Electrodeposition parameters for ZnO nanorod arrays for photovoltaic applications. Issue 8 (14th June 2013) - Ludwig, Wiebke; Ohm, Wiebke; Correa‐Hoyos, John‐Michael; Zhao, Yanmin; Lux‐Steiner, Martha Ch.; Gledhill, Sophie
Abstract To identify optimal deposition conditions and morphologies for ZnO nanorod arrays (NRA) for photovoltaic applications, ZnO NRA were electrochemically grown onto transparent conducting oxide (TCO) substrates pre‐covered with an intrinsic zinc oxide (i‐ZnO) seed layer (SL) at different cathodic potentials, deposition times and temperatures. The morphology and the optical properties of the ZnO NRA were investigated with respect to application in thin film solar cells. The NRA morphology was found to be strongly correlated with the amount of electrochemically deposited ZnO, irrespective of the reaction conditions for a wide range of parameters. It was demonstrated that also the optical reflectance and transmittance of the NRA were closely connected to the electrochemically deposited amount of ZnO and the NRA morphology. Also the relative amount of defects determined by room temperature (RT) photoluminescence (PL) measurements correlated with the amount of electrochemically deposited ZnO, higher defect densities were however found for high cathodic potentials and low temperatures presumably due to excessive deposition rates and preferential formation of Zn(OH)2, respectively. A range of reaction conditions was identified yielding both fast growth and ZnO NRA with morphological and optical properties suited for thin film solar cell applications.